The evaluation of gonadotropins (FSH, LH) and testicular pathology in infertile men - Hamid Shafi; Yousef-Reza Yousefnia Pasha; Mostafa Asgharpour (Babol University of Medical Sciences, 2016)
Background: Azoospermia is the most challenging issue associated with infertility treatment. The aim of this study was to re-examine the relationship between plasma levels of follicle stimulating hormone (FSH) and luteinizing hormone (LH) with testicular pathology in azoospermic infertile men visiting the infertility clinic in north of Iran. Methods: Fifty eligible azoospermic infertile men who had the medical indication of testicular biopsy for sperm retrieval in infertility clinic were included in the study. Plasma FSH and LH were measured by immunoassay. Then a bilateral testicular biopsy using Bouin's solution as a fixative was performed under local anesthesia. The One-way analysis of variance was used to assess the differences between the groups. Results: The plasma levels of FSH (p=0.0001) and LH (p=0.044) among infertile men with Sertoli-cell-only syndrome was significantly higher than those with hypospermatogenesis. Also, the plasma levels of FSH among infertile men with maturation arrest was significantly higher than those with hypospermatogenesis (p=0.003). There were no statistically significant differences in plasma LH levels between hypospermatogenesis and maturation arrest. Conclusions: The findings of the present study indicated that the plasma levels of FSH and LH among infertile men with azoospermia testis correlated with the histopathological features. Therefore, it is necessary to emphasize the fact that azoospermic cases with highly-elevated plasma FSH and LH levels could be excluded from separate testicular biopsy as they are not suitable cases for conventional treatments.